Reframing E-Government Development Indices with Respect to New Trends in ICT - Renáta Máchová; Martin Lněnička (Review of Economic Perspectives, 2015)
E-government readiness is an important indicator of the quality of a country's technological and telecommunication infrastructure and the ability of its citizens, businesses and governments to adopt, use and benefit from modern technologies. To measure and compare selected countries, a lot of benchmarking and ranking indices have been introduced since the beginning of the century. With the increasing importance of trends such as cloud computing, open (big) data, participation tools or social media, new indicators and approaches need to be introduced in the measuring of the e-government development, and the existing indices should to be updated, redefined and restructured. Therefore, this article explores the structure of the existing e-government development indices to show the main indicators and trends. Then, it proposes and implements a new framework to evaluate e-government development using these new trends in ICT. It also examines and compares a basic background on the e-government development, benefits and risks of cloud computing, open (big) data and participation tools in the public sector. Based on the newly proposed framework, the e-government development index is calculated for each EU Member State to clearly identify the indicators to have an influence on the e-government development. In the last part, these results are compared to the already existing indices to validate the conformity of the rank methods using Kendall rank correlation coefficient.
Keywords: 330